2014
DOI: 10.1007/s00213-014-3458-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between impulsivity and subjective response in an IV ethanol paradigm

Abstract: Rationale: Impulsivity and individual differences in subjective response to alcohol are risk factors for alcohol problems and possibly endophenotypes for alcohol dependence. Few prior studies have addressed relationships between the two constructs. Objectives: To predict subjective responses to ethanol, we tested self-reported impulsiveness, ethanol dose condition (high dose, low dose or placebo) and time (7 timepoints) along with interactions among these variables. Methods: The present study is a secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
49
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 52 publications
10
49
2
Order By: Relevance
“…Findings also showed that ADHD symptoms predicted steeper increases in stimulation, but only on the ascending limb. In contrast to prior studies of sensation seeking and related personality traits (e.g., Erblich & Earleywine, 2003; Fillmore, et al, 2009; Leeman, et al, 2014; Scott & Corbin, 2014), sensation seeking did not moderate changes in subjective stimulation. Because the association of subjective stimulant or sedative effects with motivational indicators (e.g., craving, wanting) may have etiological relevance (King, et al, 2011), further laboratory studies of these associations, including the examination of individual or pharmacological (e.g., BAC limb) moderators, is likely important.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings also showed that ADHD symptoms predicted steeper increases in stimulation, but only on the ascending limb. In contrast to prior studies of sensation seeking and related personality traits (e.g., Erblich & Earleywine, 2003; Fillmore, et al, 2009; Leeman, et al, 2014; Scott & Corbin, 2014), sensation seeking did not moderate changes in subjective stimulation. Because the association of subjective stimulant or sedative effects with motivational indicators (e.g., craving, wanting) may have etiological relevance (King, et al, 2011), further laboratory studies of these associations, including the examination of individual or pharmacological (e.g., BAC limb) moderators, is likely important.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, greater impulsivity was associated with increases in positive mood over the course of rising BrAC and as compared to the placebo. Our findings extend the work of Leeman et al (2014) by using a behavioral measure of impulsivity to demonstrate the association between impulsivity and SR in a sample of participants with AD. Furthermore, our results indicate that highly impulsive individuals with AD experience substantial increases in stimulation and hedonic reward during alcohol administration, suggesting that their alcohol consumption produces rewarding effects.…”
Section: Discussionsupporting
confidence: 75%
“…By comparison, low impulsive individuals with AD may be less sensitive to the hedonic effects of alcohol, suggesting that alternative factors may influence the drinking behavior of these individuals. Whereas Leeman et al (2014) administered a self-report measure of impulsivity, the Barratt Impulsiveness Scale (Patton et al, 1995), we used the DDT, a behavioral measure of impulsivity that may be less vulnerable to self-report bias. Given the mixed evidence regarding associations between self-report and behavioral measures of impulsivity, the high level of consistency between these data and those reported by Leeman et al (2014) suggests that the association between impulsivity and SR is generalizable and robust to protocol changes (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations